Effects of intention understanding and brief imitative experience on the mirror neuron system: An EEG study using Japanese sign language - Tomoki Osaki; Takehiro Minamoto (PLoS ONE, 2025)
The mirror neuron system (MNS) is the neural system that activates when individuals both observe and execute an action. Previous studies consistently indicate that the MNS is also involved in intention understanding. In addition, MNS activity is augmented after imitating an unfamiliar action. However, it remains unclear whether conscious effort to interpret an actors’ intention further activates the MNS, consequently promoting action learning. To investigate an interactive effect between intention understanding and imitative experience of unfamiliar actions, the present study measured EEG while participants observed Japanese sign language and while they imitated signing. To manipulate a level of intention understanding, we prepared two tasks: the counting task required participants to count the number of body movements in sign language, and the meaning task required participants to guess the meaning of sign language. Mu suppression, one of the indices of the MNS, was measured during three phases: pre-imitation, imitation, and post-imitation. The results revealed that the magnitude of mu suppression was comparable between the two tasks, and remained unchanged in the pre- and post-imitation phases. The null effect of the imitative experience may be attributable to cultural factors as gestural communication is less encouraged in Japanese culture, making it challenging for the MNS to learn new actions. Furthermore, absence of an effect from the task may be attributed to greater number of unfamiliar movements in sign language, resulting in the MNS preferentially processing body movements rather than the intention of actors.